A review on investigating the role of block-chain in cyber security. (2022) - Aggarwal, Bharat Kumar; Gupta, Ankur; Goyal, Deepak; Gupta, Pankaj; Bansal, Bijender; Barak, Dheer Dhwaj
Abstract: In the issue of cyber security, block-chain, which is best known for crypto currencies, is providing an interesting answer. Block-chain has excellent safeguards against information manipulation. It supports securing access to Internet of Things (IOT) devices. Furthermore, it enables hacked IOT network instruments to be closed and unplugged. Block-chain serves as a distributed ledger system. It is used in conjunction with IOT to enable machine-to-machine interactions. It makes use of a database that contains a collection of transactions. These transactions are double-checked and recorded in a central ledger. On each node, these ledgers have been deployed. The idea of block chain is discussed in conjunction with the Internet of Things in this research study. Several studies in the fields of block-chain and IOT are considered in this paper. The necessity for block-chain and its development have been discussed in terms of its applicability difficulties. In addition, the significance of block chain in IOT-based research for online transaction security is examined.